2021
DOI: 10.1504/ejim.2021.113271
|View full text |Cite
|
Sign up to set email alerts
|

Sport as a vehicle for implementing corporate social responsibility: firms listed on the Warsaw and Moscow stock exchanges

Abstract: This paper provides a descriptive account of the extent to which firms listed on the Warsaw (WSE) and Moscow (MSE) Stock Exchanges use sport for their corporate social responsibility agendas. Drawing on institutional isomorphism, we deductively categorised CSR through sport cases based on the framework developed by Bason and Anagnostopoulos (2015). A total of 1,317 documents were content-analysed, 442 from WSE firms and 875 from MSE firms. A total of 2,501 CSR-through-sport initiatives were reported over the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Raimo et al (2021) advocate that CSR can be applied as a legitimation strategy in football clubs. Anagnostopoulos et al (2021) argue that sports can be used as a means for CSR implementation.…”
Section: Stakeholder Management and Corporate Social Responsibility Csfmentioning
confidence: 99%
“…Raimo et al (2021) advocate that CSR can be applied as a legitimation strategy in football clubs. Anagnostopoulos et al (2021) argue that sports can be used as a means for CSR implementation.…”
Section: Stakeholder Management and Corporate Social Responsibility Csfmentioning
confidence: 99%
“…All this is often referred to as sport-fordevelopment (SfD), which has been defined as "the use of sport to exert a positive influence on public health, the socialization of children, youths, and adults, the social inclusion of the disadvantaged, the economic development of regions and states, and on fostering intercultural exchange and conflict resolution" (Lyras and Welty Peachey, 2011, p. 311).Depending on how much emphasis is placed on sport and/or developmental outcomes, Coalter (2010) suggested that SfD programs can be classified along a continuum: (a) Sport: in its traditional form, sport implies that it possesses fundamental developmental properties for its participants; (b) Sport-plus involves modifying sports (and sometimes combining them with other programs) to achieve broader developmental objectives and (c) Plus-sport uses sport as an enticement to encourage participants to participate in development activities (non-sport outcomes).Either of these SfD programs increasingly falls under the broader social responsibility agendas of firms outside the sports ecosystem (Levermore, 2010). Indeed, several studies have empirically confirmed (see, for example, Anagnostopoulos et al, 2021;Bason and Anagnostopoulos, 2015;McDonald et al, 2009) what Smith and Westerbeek (2007) argued that corporate social responsibility (CSR) programs are best developed and implemented through sport. As the World Business Council for Sustainable Development explains, CSR is a commitment by businesses to behave ethically, contribute to economic growth and improve the quality of life for employees, their families, their communities and society as a whole.…”
mentioning
confidence: 97%
“…Either of these SfD programs increasingly falls under the broader social responsibility agendas of firms outside the sports ecosystem (Levermore, 2010). Indeed, several studies have empirically confirmed (see, for example, Anagnostopoulos et al, 2021;Bason and Anagnostopoulos, 2015;McDonald et al, 2009) what Smith and Westerbeek (2007) argued that corporate social responsibility (CSR) programs are best developed and implemented through sport. As the World Business Council for Sustainable Development explains, CSR is a commitment by businesses to behave ethically, contribute to economic growth and improve the quality of life for employees, their families, their communities and society as a whole.…”
mentioning
confidence: 97%